Answer:
x = 6
Step-by-step explanation:
Start off by reducing this equation: divide all three terms by 4. This yields:
x^2 - 12x + 36 = 0
This equation has the form (x - h)^2, the square of a binomial.
x^2 - 12x + 36 = 0, written as the square of the binomail x - 6, comes out to:
(x - 6)^2 = 0. This equation has a repeated real root: x = 6
Answer:
No matter the number, the tenths place is the first to the right of the decimal point. In numbers with no decimal point, the tenths place is zero.
Step-by-step explanation:
Answer:
Because it is a tenth of one whole
Step-by-step explanation:
When one is divided by ten, it is called a tenth, a piece of a whole
Step-by-step explanation:
x² - 2 = 2^(2/3) + 2^(-2/3)
x² = 2^(2/3) + 2 + 2^(-2/3)
x² = (2^(1/3))² + 2 × 2^(1/3) × 2^(-1/3) +
(2^(-1/3))² (It is in the form of a²+2ab+b²)
x² = (2^(1/3) + 2^(-1/3))²
x = 2^(1/3) + 2^(-1/3)
B 6
C 3
The base is 6.
In order to find this, we can set the legs equal to each other since legs have the same length in an isosceles triangle.
x + 1 = -x + 7
2x + 1 = 7
2x = 6
x = 3
Now that we have the value for x, we can plug into the equation to get the value for the base.
3x - 3 = base
3(3) - 3 = base
9 - 3 = base
6 = base